Agency theory, ownership structure and capital structure: an empirical investigation in the Indian automobile industry / Vibha Tripathi - Tripathi, Vibha (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, Shah Alam, 2019)
Capital structure is not only the result of the various financial characteristics of the firm but is also determined by the decision makers. The study from the perspective of the Agency Theory, examines the relationship between ownership structure and the capital structure of the Automobile Industry in India from 2001 to 2014 by using panel data analysis. Debt Equity Ratio represented capital structure and Promoters Shareholding wasused as a proxy for ownership structure. The findings of the study after controlling for variables like assets turnover ratio, uniqueness and size reveal that ownership structure has a significant and positive relationship with capital structure showing postulates of the Agency Theory. The findings lend new insights to the fact that a majority of the Indian automobile firms which are family oriented promote the use of debt to mitigate agency costs unlike the popular belief that Indian firms follow the Pecking Order Theory. The existence of the Agency Theory signals to the probable investors about the managers-shareholders as well as shareholders-debtholders relationship, and its impact on company’s debt taking capacity.